2022
DOI: 10.1371/journal.pone.0272417
|View full text |Cite
|
Sign up to set email alerts
|

Promising FDA-approved drugs with efflux pump inhibitory activities against clinical isolates of Staphylococcus aureus

Abstract: Background and objectives Staphylococcus aureus is an opportunistic pathogen that causes wide range of nosocomial and community-acquired infections which have spread worldwide leading to an urgent need for developing effective anti-staphylococcal agents. Efflux is an important resistance mechanism that bacteria used to fight the antimicrobial action. This study aimed to investigate the efflux mechanism in S. aureus and assess diclofenac, domperidone, glyceryl trinitrate and metformin as potential efflux pump i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…And it has reported that secondary active transporters are highly substrate specific and their recognition sites are often antimicrobial drug targets ( Figure 5 and Table 5 ). 111 …”
Section: Resistance Mechanisms Of Mrsamentioning
confidence: 99%
See 1 more Smart Citation
“…And it has reported that secondary active transporters are highly substrate specific and their recognition sites are often antimicrobial drug targets ( Figure 5 and Table 5 ). 111 …”
Section: Resistance Mechanisms Of Mrsamentioning
confidence: 99%
“…And it has reported that secondary active transporters are highly substrate specific and their recognition sites are often antimicrobial drug targets (Figure 5 and Table 5). 111 MFS is the largest and most diverse membrane protein transport family, as well as the most well-studied efflux pump, which mainly includes norA, norB, norC, tet(K), tetL, mdeA, sdrM, qacA/B and other genes. Members of MFS have 12/ 14 monomeric proteins with transmembrane-spanning (TMS) helices ranging from 388 to 600 amino acids in length.…”
Section: Active Efflux Mechanismmentioning
confidence: 99%
“…Researchers have explored potential FDA-approved EPIs against clinical Staphylococcus aureus, as well as natural compounds to target MefA/E-pumps in drug-resistant bacteria; however, the same were not translated clinically. The structural insights from the present study can be instrumental in phenotypic studies on macrolide resistance in pneumococci and also in designing potent EPIs translatable to the clinics.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is limited research on model organisms to test EPIs, and there is limited data from patients to show that EPIs can be successfully used. So far, C. elegans , G. melonella , D. melanogaster , and zebrafish have been successfully used as model organisms to study various efflux pumps, while murine models showed mixed results [ 140 , 167 , 168 , 169 , 170 ].…”
Section: Known Epismentioning
confidence: 99%